Peningkatan Kapasitas Wirausaha dan Pemanfaatan Media Sosial sebagai Sarana Promosi Produk bagi Ibu Rumah Tangga - Mai Yuliastri Simarmata; Rini Agustina; Fitriani; Yuyun Safitri; Ramadhan Kusuma Yuda (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This Community Service (PKM) activity aims to improve the entrepreneurial capacity and ability to utilize social media as a means of product promotion for housewives at P.H. Mukhsin Mega Mas, Sungai Raya Dalam, Kubu Raya Regency. Based on pre-observations, it was found that most participants had never attended formal entrepreneurship training, lacked understanding of product marketing strategies, and had not yet optimally utilized social media to support their businesses. The activity was implemented through training and mentoring methods, including an introduction to local product-based business opportunities, digital marketing strategies, and practical use of social media for product promotion. The activity involved 15 housewives who owned micro-enterprises. The results of the activity showed an increase in the participants' understanding of business management and digital marketing. Furthermore, participants began to develop the ability to create simple promotional content and utilize social media as a means of product marketing. This activity is expected to increase entrepreneurial motivation, expand marketing reach, and support sustainable family economic growth.